Analisis efektivitas public relation terhadap reputasi bank syariah di tengah persaingan industri keuangan - Ash Shiddiqi, M. Zidan Fahmi (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the effectiveness of the role of Public Relations (PR) in building and strengthening the reputation of Islamic banks amid increasing competition in the financial industry, especially in the digital era that demands transparency and speed of information. The background of this study is based on the phenomenon that the reputation of Islamic financial institutions is not only influenced by financial performance, but also by the institution’s ability to manage public communication strategically, consistently, and in accordance with Islamic values such as sidq (honesty), amanah (responsibility), and tabligh (correct communication). The research method used is descriptive qualitative with a literature study approach and theoretical analysis of the concepts of PR, reputation, and Islamic communication principles in the context of Islamic banking. The results of the analysis show that high PR effectiveness contributes significantly to the formation of a positive image, increased customer trust, and strengthening the institution’s reputation in the public eye. In addition, the application of digital public relations strategies through social media and online platforms has proven to be an important factor in expanding the reach of communication and maintaining a two-way relationship with the community. This study confirms that the success of PR in Islamic banks lies not only in product promotion, but also in the integration of spiritual and ethical values in all communication activities. Thus, strengthening the capacity of the PR division and implementing sharia-based communication strategies in the digital era are strategic requirements for the sustainable improvement of the reputation of sharia financial institutions.